Diagnosis of venous disease with duplex ultrasound. (March 2013) - Malgor, R D; Labropoulos, N
The advent of duplex ultrasound (DU) has changed vascular practice over the years. Venous anatomy, valve function and obstruction can be evaluated in real time using DU. It is a low cost, portable, non-invasive, safe and operator-friendly device that can be used for diagnosis, treatment guidance and follow-up. This paper defines the patterns, location and characteristics of venous reflux and also provides insightful information on acute and chronic venous obstruction.